Faktor-Faktor Yang Mengaruhi Kinerja Karyawan Hotel 88 di Jakarta - Fetty Asmaniati; Ismeth Emier Osman; Anita Swantari; Haryo Wicaksono; Candra Hidayat; Mira Maharani (Program Studi Manajemen Divisi Kamar, 2023)
This study aims to determine salary, incentives and work motivation on employee performance. Quantitative descriptive is this type of research, using several analytical methods. The unit of analysis is hotel 88 employees consisting of Hotel 88 Mangga Besar 120 employees, Hotel 88 Mangga Besar VIII employees and Hotel 88 Fatmawati employees using accidental sampling. The population in this study were all employees at Hotel 88. The sample in this study was 100 respondents. The results of the study show that salary, incentives and work motivation have a significant effect on employee performance. Salary is useful for employees to meet their daily needs. Employee incentives can increase employee work productivity as a reward for Hotel 88 work performance. Work motivation provides comfort for employees to continue working at Hotel 88 because the work environment is comfortable and safe.